Family Business Succession In Agricultural Sector: Affection And Memorable Experience - Yasmin Puspitasari; Noermijati Noermijati; Radityo Putro Handrito (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Agriculture is one of the sectors that dominates family businesses, yet it now faces major challenges in succession and sustainability due to the declining interest of younger generations in continuing agricultural enterprises. Within this context, the study highlights a unique paradox in the process of family business succession in the agricultural sector of Batu City, East Java. Drawing on Social Cognitive Theory, Institutional Logic Theory, and Social Exchange Theory, this research examines how succession and sustainability are shaped within family-run agricultural enterprises managed by young successors. Using a qualitative phenomenological approach, the study explores in depth the lived experiences of the participants. The findings reveal that parental affection, moral guidance, experiences of loss, filial devotion, and childhood memories play crucial roles in shaping the readiness of the younger generation to sustain the family business. This research contributes to the development of human resource management studies by integrating multidisciplinary perspectives and demonstrating that the sustainability of family businesses is determined not only by economic capability but also by the strength of family values and emotional bonds. The findings provide direction for policymakers to strengthen youth motivation and ensure sustainable agricultural regeneration in Indonesia. KEYWORDS: Family Business Succession; Family Role; Young Generation; Family Values and Traditions; Agricultural Sustainability